Simplified methodologies to designate sensitive areas and nitrate vulnerable zones: A case study of Yesilirmak River Basin, Turkey. Issue 1 (13th December 2021) - Ayaz, Selma; Atasoy Aytış, Elif; Koyunluoğlu Aynur, Şebnem; Kıran, Burcu; Beşiktaş, Mehmet; Sarıkaya, Ömer; Karaaslan, Yakup
Abstract: The European Union enforces the member states designate sensitive areas and nitrate vulnerable zones according to Water Framework Directive and its daughter directives Nitrates Directive and Urban Wastewater Treatment Directive. The aim of this study is to develop an approach for designation of sensitive areas (SAs) and nitrate vulnerable zones (NVZs) for surface water bodies. SAs are designated with a three‐step approach using initial characterization, physicochemical monitoring, and application of biotic indices. Nitrate concentration data of monitoring stations and the total nitrate loading rates of agriculture were two parameters for the determination of NVZs. This simplified methodology was applied to Yesilirmak River Basin. A total of 42 water bodies (23 river and 19 lake) were specified as SA and 30 water bodies (17 river and 13 lake) were designated as NVZ which constitutes about 63% and 49% of the total drainage area of the basin, respectively. Although the final definition of SAs and NVZs will depend on policies and regulations adopted in Turkey, the study contributed to efforts of Turkish water authorities for the determination of the SAs and NVZs of Turkey.